African Human Rights Law Reports 2008 - Edited by The African Commission on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria (Pretoria University Law Press (PULP), 2010)
African Human Rights Law Reports 2008 Edited by The African Commission on Human and Peoples' Rights & the Centre for Human Rights, University of Pretoria 2010 ISSN: 1812-2418 Pages: xxxviii 284 Print version: Available Electronic version: Free PDF available